Botrytis cinerea BcCDI1 protein triggers both plant cell death and immune response - Zhu, Wenjun; Dong, Huange; Xu, Ran; You, Jingmao; Yan, Da-zhong; Xiong, Chao; Wu, Jing; Bi, Kai (Frontiers in Plant Science, 2023)
Cell-death-inducing proteins (CDIPs) play important roles in the infection of Botrytis cinerea, a broad-host-range necrotrophic phytopathogen. Here, we show that the secreted protein BcCDI1 (Cell Death Inducing 1) can cause necrosis in tobacco leaves and at the same time elicit plant defense. The transcription of Bccdi1 was induced at the infection stage. Deletion or overexpression of Bccdi1 resulted in no notable change in disease lesion on bean, tobacco and Arabidopsis leaves, indicating that Bccdi1 has no effect on the final outcome of B. cinerea infection. Furthermore, the plant receptor-like kinases BAK1 and SOBIR1 are required to transduce the cell death-promoting signal induced by BcCDI1. These findings suggest that BcCDI1 is possibly recognized by plant receptors and then induces plant cell death.